Jet lag and travel fatigue: a comprehensive management plan for sport medicine physicians and high-performance support teams - Samuels, C. H. (Clinical Journal of Sport Medicine, 2012)
The impact of transcontinental travel and high-volume travel on athletes can result in physiologic disturbances and a complicated set of physical symptoms. Jet lag and travel fatigue have been identified by athletes, athletic trainers, coaches, and physicians as important but challenging problems that could benefit from practical solutions. Currently, there is a culture of disregard and lack of knowledge regarding the negative effects of jet lag and travel fatigue on the athlete`s well-being and performance. In addition, the key physiologic metric (determination of the human circadian phase) that guides jet lag treatment interventions is elusive and thus limits evidence-based therapeutic advice. A better understanding of preflight, in-flight, and postflight management options, such as use of melatonin or the judicious application of sedatives, is important for the sports clinician to help athletes limit fatigue symptoms and maintain optimal performance. The purpose of this article was to provide a practical applied method of implementing a travel management program for athletic teams.